Reducing the Divorce Rate in the Religious Courts Through Cultivating Egalitarian Relationships - Ulin Na’mah; Mochammad Agus Rachmatulloh; Husnul Yaqin; Rezki Suci Qamaria (UIN Sunan Gunung Djati, 2024)
The income factor is often the reason for divorce by petition, a phenomenon of high divorce rates in Indonesia. Furthermore, this problem has resulted in various analytical results. It is very embarrassing that all these analyses tend to blame one party, namely that often, the wife is blamed without presenting writings about wise efforts to resolve relationship problems that lead to mutualism. Apart from that, previous researchers were still trapped in understanding the husband-and-wife relationship as a relationship that was nothing more than a matter of the rights and obligations of husband and wife, which were considered absolute. Even though the perspective of interdependence as something prescribed in Islam has begun to be discussed, there has been no study or offer on how to improve the pattern of interdependence in the lives of husbands and wives. This research aims to provide a practical way to create an egalitarian relationship between husband and wife by first uncovering the causes of the difficulty of implementing an egalitarian pattern in husband-and-wife relationships, which is a factor in the increase in divorce cases due to income reasons. This research uses an empirical or psychological phenomenological approach based on Gary Chapman's